The Application of UTY and SRY Molecular Markers for Determination of Unknown Sex Samples in Bali Cattle - Indriawati, Indriawati; Volkandari, Slamet Diah; Margawati, Endang Tri (Jurnal ILMU DASAR, 2020)
An investigation involving large number of animals is often resulting incomplete or in accurate information such as animal parentage, or misidentify on sex due to unlabeled sex samples. A PCR method by applying Y chromosome markers (UTY and SRY) facilitates in determination of unknown sex problem. This study was intended to determine sex from unlabelled sex of blood samples by applying PCR method using a pooled-DNA template. Twenty five of unknown sex blood samples from Nusa Penida, Bali were used in this study. The samples were plotted into 5 pooled-DNA whith each pool DNA consisted of 5 individuals DNA. Two pairs of sex primers, UTY (58oC) and SRY (60oC) with 35 cycles were applied to amplify the samples. The result showed there was only one pooled-DNA (P4) amplified by UTY (484bp). Whereas re-PCR of the positive pooled-DNA (P4) using SRY primer, only one out of 25 samples determined as male Bali cattle (325bp). This finding suggests that UTY and SRY primers are suitable for sex determination and the pooled-DNA could be used as an efficient PCR method both in consumables and PCR process for sex determination. Keywords: Determination, sex, unknown sample, pooled DNA, Bali cattle.